Islam dan Resolusi Konflik - Muhamad Harjuna (Religi: Jurnal Studi Agama-agama, 2018)
AbstractThis article examines the essence of religion and specifically speaks of Islam as a peaceful, progressive and solutive religion. Islam comes from the Most Peaceful (al-Salâm), always spreading peace wherever and whenever. The greetings spoken by Muslims reflect the noble character of the Assalamu'alaikum (may peace be upon you). Islam is a progressive religion, against oppressors, capitalists, injustices, fighting for the rights of the oppressed little ones, glorifying women, and bringing about a harmonious and peaceful society within the framework of fraternity. Islam is a solutive religion, teaches the virtues of morality as opposed to bad morality, resolves nonviolent conflict, and contributes to giving spirit to build peace or conflict resolution, and also contributes in giving spirit to build peace or conflict resolution. The Qur'an’s solution to conflict is a suggestion for clarification, mediation, deliberation, forgiveness, reconciliation, good deeds, and justice. A holistic study of Islam will find the substance of Islam as a religion of  raḥmatan lil 'âlamḭn.